Association between vitamin D serum levels and insulin resistance assessed by HOMA-IR among non-diabetic adults in the United States: Results from NHANES 2007–2014 - Yin, Xin; Chen, Jia-Yu; Huang, Xiang-Jie; Lai, Jia-Hong; Huang, Chang; Yao, Wang; Li, Nan-Xi; Huang, Wei-Chao; Guo, Xu-Guang (Frontiers in Nutrition, 2022)
Insulin resistance, a pathological response to insulin hormone in insulin-dependent cells, is characterized by the presence of high glucose and insulin concentrations. The homeostasis model of insulin resistance (HOMA-IR) is one of the most used indexes to estimate insulin resistance by assessing the fasting glucose and insulin levels. An association was observed between vitamin D levels and insulin resistance, which varied in different ethnic groups, and there is some evidence that vitamin D supplementation could contribute to the improvement of insulin resistance. This study assessed the association between 25-hydroxyvitamin D (25[OH]D) concentration and HOMA-IR in American adults aged 20 years and older, without diabetes and other chronic diseases that can influence insulin resistance. The data from the National Health and Nutrition Examination Survey (NHANES) 2007–2014 were used by exploiting the free and publicly-accessible web datasets. Linear regression models were performed to evaluate the association between serum 25(OH)D concentration and HOMA-IR, and a negative association was observed, which remained significant following the adjustment for age, gender, race/ethnicity, education, body mass index (BMI), physical activity, the season of examination, current smoking, hypertension, the use of drugs which can influence insulin resistance, serum bicarbonates, triglycerides, and calcium and phosphorus levels. Only in non-Hispanic Blacks was this inverse association between vitamin D and HOMA-IR not observed in the fully adjusted model. Further studies are needed to explain the mechanisms of the observed ethnic/racial differences in the association of vitamin D levels with HOMA-IR.